Ovarian Cancer From Pathogenesis to Treatment - Devaja, Omer; Papadopoulos, Andreas (IntechOpen, 2018)
Ovarian cancer management is a rapidly changing field with new treatment agents available as a result of a greater understanding of the pathogenesis of this disease. In addition, both surgical and chemotherapeutic treatment strategies are evolving to maximise response in this disease. This book brings together leading specialists from around the world to discuss and outline a variety of new concepts in ovarian cancer, ranging from molecular biology and genetics through screening to both surgical and chemotherapeutic management.